Righteous indignation : excuse me while I save the world - Breitbart, Andrew (Grand Central Pub., 2011)
Known for his network of conservative Web sites, Breitbart talks about the key issues that Americans face, how he has aligned himself with the Tea Party, and how one needs to deal with the liberal news world head on.